Use of Topical Minoxidil, 17α-Estradiol and Hydrocortisone Butyrate in Frontal Fibrosing Alopecia. (May 2014) - Rossi, A.; Iorio, A.; Scarnò, M.; Fortuna, M.C.; Priolo, L.; Di Nunno, D.; Carlesimo, M.; Calvieri, S.; Mari, E.
A valid approach to treating frontal fibrosing alopecia (FFA), a scarring alopecia, does not yet exist. The aim of this study is to evaluate the efficacy of a topical application composed of minoxidil, hydrocortisone butyrate, 17α-estradiol, ciclosilicone pentamer, and alcohol in women affected by FFA. Forty women affected by FFA were treated with 2 ml of a topical lotion composed of 2% minoxidil base, 0.08% hydrocortisone butyrate, 0.05% 17α-estradiol, 16% ciclosilicone pentamer, 96° alcohol, applied once a day on the scalp. A score index, based on the comparison of the photos, taken at the beginning (T0) and after 36 months (T36), was used. The topical lotion led to an improvement in 20 patients, stabilization in 15 patients and worsening of the clinical condition in 5 women. This topical lotion induces a considerable improvement or stabilization of frontal fibrosing alopecia.